The process of disclosing a diagnosis of dementia and mild cognitive impairment: A national survey of specialist physicians in Denmark. (April 2020) - Nielsen, T Rune; Svensson, Birthe Hjorth; Rohr, Gitte; Gottrup, Hanne; Vestergaard, Karsten; Høgh, Peter; Waldemar, Gunhild
Background: Although general recommendations for diagnostic disclosure of dementia are available, little is known about how these recommendations are implemented. The aim of the current study was to investigate the process and content of dementia diagnostic disclosure meetings, and to compare key aspects of disclosing a diagnosis of dementia and mild cognitive impairment. Method: A total of 54 specialist physicians in Danish dementia diagnostic departments completed an online survey on their practices regarding diagnostic disclosure of dementia and mild cognitive impairment. The influence of respondent characteristics was assessed, and differences on key aspects of disclosing a diagnosis of dementia and mild cognitive impairment were analyzed. Results: The results suggest that among Danish specialist physicians, there is a general consensus regarding the organization of diagnostic disclosure meetings. However, differences in employed terminology and information provided when disclosing a dementia diagnosis were evident. Significant differences were present on key aspects of the diagnostic disclosure of dementia and mild cognitive impairment. For instance, 91% would use the term dementia during diagnostic disclosures compared to just 72% for mild cognitive impairment. Conclusion: The range of practices reflected in the present study confirms the complexity of diagnostic disclosure and highlights the importance of preparation and follow-up strategies to tailor the disclosure process to the needs of individual patients with dementia and their caregivers. Due to earlier diagnosis of neurodegenerative disorders, more research is urgently needed on this aspect of the diagnostic process, especially to develop evidence-based models for the disclosure of mild cognitive impairment.